Inpatient Case Report: Severe Malaria - D. Insantuan, Odilia; Regina Manubulu, Maya; B. Tokan, Hendrik (Green Publisher Indonesia, 2024)
Malaria is a significant global health problem caused by Plasmodium parasites transmitted through Anopheles mosquito bites, predominantly affecting tropical and subtropical regions. This case report focuses on a pediatric patient with severe malaria caused by Plasmodium falciparum at Prof. Dr. W.Z. Johannes Hospital, Kupang, Indonesia. The patient, a 7-year-old girl, presented with fever, vomiting, reduced appetite, and decreased consciousness. Laboratory tests revealed severe anemia, liver dysfunction, and positive malaria microscopy for P. falciparum. The study employed a comprehensive clinical approach, combining patient history, physical examination, and laboratory tests to diagnose and manage the condition. Treatment included intravenous fluids, antimalarial drugs, and supportive care. The results underscore the importance of prompt diagnosis and treatment in severe malaria cases to mitigate life-threatening complications like cerebral malaria, which is associated with high mortality rates. This case highlights the pressing need for tailored malaria management strategies, particularly in resource-limited settings. Conclusively, timely and targeted interventions can effectively address severe complications, ensuring better outcomes in malaria-endemic regions.